2018
DOI: 10.5713/ajas.17.0217
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cooking method and final core-temperature on cooking loss, lipid oxidation, nucleotide-related compounds and aroma volatiles of Hanwoo brisket

Abstract: ObjectiveThis study observed the effects of cooking method and final core temperature on cooking loss, lipid oxidation, aroma volatiles, nucleotide-related compounds and aroma volatiles of Hanwoo brisket (deep pectoralis).MethodsDeep pectoralis muscles (8.65% of crude fat) were obtained from three Hanwoo steer carcasses with 1+ quality grade. Samples were either oven-roasted at 180°C (dry heat) or cooked in boiling water (moist heat) to final core temperature of 70°C (medium) or 77°C (well-done).ResultsBoiling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Though traditionally cooked sample (CON75) was cooked at high temperature of 75°C and with the presence of oxygen, the samples in the traditional cooking method had better water retention than the sous vide samples, except for SV45. Cooking time had a significant effect on these parameters [21,33]. Thus, samples cooked for less time (traditional cooking method) showed less water loss than samples cooked for 6 h (SV45–65).…”
Section: Resultsmentioning
confidence: 99%
“…Though traditionally cooked sample (CON75) was cooked at high temperature of 75°C and with the presence of oxygen, the samples in the traditional cooking method had better water retention than the sous vide samples, except for SV45. Cooking time had a significant effect on these parameters [21,33]. Thus, samples cooked for less time (traditional cooking method) showed less water loss than samples cooked for 6 h (SV45–65).…”
Section: Resultsmentioning
confidence: 99%
“…The meat samples were cooked when the oven temperature reached 200 ºC for 15 minutes and 9 minutes respectively. All cooked meat samples were processed until the internal core temperature of beef and chicken reached 77 ºC (well-done) and 70 ºC respectively using a digital thermometer (Oz et al, 2016;Utama et al, 2018). The meat samples were packed and stored in a sealed vacuum-packed and moisture impermeable polyethylene plastics and stored at -4 ºC in a freezer for a five-day period.…”
Section: Samples Preparationmentioning
confidence: 99%
“…The higher cook loss in samples that were cooked using the griddle may be due to the longer cooking time as this cooking method is by contact between the hot surface and the MPC and the main method of heat transfer is via conduction. It was reported that different cooking methods have significant effects on the physicochemical changes due to the cook loss of meat products that affect the cooking times, temperatures and methods of heat transfer(Ishiwatari et al 2013;Bejerholm & Aaslyng, 2004).Alfaia, Alves, Lopes, Fernandes, Costa et al (2010) andUtama, Baek, Jeong, Yoon, Joo et al (2018) reported increased cook loss when beef was oven roasted rather than boiled due to prolonged heat exposure duration.…”
mentioning
confidence: 99%